Spectrophotometric Reaction Rate Method for the Determination of Ultra Trace Amounts of Rhodium by its Catalytic Effect on the Oxidation of Thionine by Metaperiodate in Micellar Media - KEYVANFARD, MOHSEN (Asian Journal of Chemistry, 2010)
A simple kinetic spectrophotometric method was developed for the determination of ultra trace amounts of Rh(III). The method is based on the catalytic effect of rhodium(III) on the oxidation of thionine by periodate at pH 6.2 in micellar media. The reaction was monitored spectrophotometrically by measuring the decrease in absorbance of thionine at 599 nm with a fixed-time method. The decrease in the absorbance of thionine is proportional to the concentration of Rh(III) in concentration range 6.0 × 10-4 - 0.080 μg/mL and 0.080-0.50 μg/mL with a fixed time of 0.5-4.5 min from initiation of the reaction. The limit of detection is 0.29 ng/mL Rh(III). The relative standard deviation of 0.020 and 0.05 μg/mL Rh(III) was 2.29 and 1.42 %, respectively. The method was applied to the determination of rhodium in water.